ANALYSIS OF IMPLEMENTATION OF REGIONAL PROPERTY MANAGEMENT IN INCREASING REGIONAL ORIGINAL INCOME IN NORTH GORONTALO DISTRICT - Kamus Ramdan Musmin; Anis Naki; Ayu Anastasya Rachman (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
The research objectives are: (1) Knowing and analyzing the management of BMD in increasing PAD. (2) Knowing and analyzing the factors that determine the management of BMD in increasing PAD. This study uses a qualitative descriptive approach, which is to examine, analyze and describe the data. The number of informants in this study was 9 people. Research Results: Management of BMD: (a) Planning; The regional government RKBMD is determined by the Property Manager (b) Utilization; utilization cooperation has not been carried out; (c) Administration; in general it has been done but there are still unclear origins of BMD goods (d) Control; it has been done but there are still findings from the BPK regarding some missing items. Conclusion: (1) The regional government has carried out BMD management, although there are still shortcomings, this can be seen in the BPK recommendations. (2) The most prominent determining factors in the management of BMD are, government policies, human resources, and the budget will be overcome if the policies that regulate it are strong and can be implemented. Suggestions: (1) In order to optimize PAD revenue, it is recommended to use BMD through rental and KSO, daily or hourly rental, and KSO with BUMdes for the management of tourist attractions; (2) It is deemed necessary to conduct an inventory of BMD every year, to find out the existence of the BMD